Aminal‐based Hypercrosslinked Polymer Modified with Small Palladium Nanoparticles for Efficiently Catalytic Reduction of Nitroarenes. Issue 20 (28th August 2018) - Xu, Dan; Wang, Fushan; Yu, Guiqin; Zhao, Hong; Yang, Jing; Yuan, Man; Zhang, Xiaoyun; Dong, Zhengping
Abstract: Fabrication of heterogeneous catalysts with excellent activity, selectivity and stability is significant for various catalytic applications. Here, we prepared a hypercrosslinked polymer (HCP) via a facile and cost‐effective strategy using ferrocenecarboxaldehyde and melamine as building blocks. Then, the HCP was modified with highly dispersed ultrafine Pd nanoparticles (Pd/HCP). The obtained Pd/HCP shows excellent catalytic activity in the catalytic reduction of nitroarenes under mild reaction conditions. It′s worth mentioning that the N atoms in the HCP can efficiently coordinate Pd ions to form small Pd nanoparticles (NPs) and subsequently prevent the aggregation and leaching of Pd NPs during the reaction, so the Pd/HCP catalyst is highly stable and can be reused at least eight cycles without loss of catalytic activity. Therefore, this work may provide possibilities for using HCPs as ideal supporting materials for fabricating highly stable and efficient heterogeneous catalysts. Abstract : Aminal kingdom ! A highly active Pd/HCP catalyst was prepared via a facile and low‐cost strategy. Ultrafine Pd NPs were stably anchored on the HCP surface with high dispersity. The Pd/HCP catalyst shows excellent catalytic performance for catalytic reduction of nitroarenes.